MENGANALISIS KESESUAIAN LATIHAN DAN EVALUASI DALAM MODUL DEUSTCH FÜR KLASSE XI BERDASARKAN TUJUAN PEMBELAJARAN - Syakirina, Azza Akira; Tampubolon, Erlika; Situmeang, Marisa Septiana; Sidabutar, Putri Angelina; Sababalat, Catherine Vanesa (Universitas Pattimura, 2025)
Exercises in language learning have an important role in improving students' language skills. This study aims to analyze the suitability of exercises and evaluations in the Deutsch für Klasse XI module with the standards set out in Permendikbud No. 37 of 2018. The research method used is document analysis with descriptive qualitative approach. Data were collected from the Deutsch für Klasse XI module as well as related educational policy documents, then analyzed to identify the extent of conformity between the exercises in the book and the expected learning outcomes. The results show that the book has provided various types of exercises that aim to improve learners' linguistic skills, ranging from reading comprehension, grammar, to speaking and writing skills. The exercises include family identification, sentence completion, listening and speaking exercises, as well as information and letter writing exercises. However, the analysis also found that some aspects in this book are still not fully in line with the national curriculum standards. In conclusion, although the Deutsch für Klasse XI module has provided enough exercises to support German language learning, there are still some aspects that need to be improved. The development of more diverse and contextualized materials is needed so that learners not only understand the structure of the language, but also can use the language in their own way.